Design and Experimental Verification of Linear Switched Reluctance Motor with Skewed Poles - Lenin N C; Arumugam R (Institute of Advanced Engineering and Science, 2015)
This paper presents the realization and design of a linear switched reluctance motor (LSRM) with a new stator structure. One of the setbacks in the LSRM family is the presence of high force ripple leads to vibration and acoustic noise. The proposed structure provides a smooth force profile with reduced force ripple. Finite element analysis (FEA) is used to predict the force and other relevant parameters.A frequency spectrum analysis of the force profile using the fast Fourier transform (FFT) is presented.The FEA and experimental results of this paper prove that LSRMs are one of the strong candidates for linear propulsion drives.